Attenuated phase shift mask for extreme ultraviolet: Can they mitigate three-dimensional mask effects? - Erdmann, Andreas; Evanschitzky, Peter; Mesilhy, Hazem Mohamed Safwat; Philipsen, Vicky; Hendrickx, Eric; Bauer, Markus (Journal of Micro-Nanolithography MEMS and MOEMS, 2019)
The understanding, characterization, and mitigation of three-dimensional (3-D) mask effects including telecentricity errors, contrast fading, and best focus shifts become increasingly important for the performance optimization of future extreme ultraviolet (EUV) projection systems and mask designs. We explore the potential of attenuated phase shift mask (attPSM) to mitigate 3-D mask effects and exploit them for future EUV imaging. The scattering of light at the absorber edges results in significant phase deformations, which impact the effective phase and the lithographic performance of attPSM for EUV. Rigorous mask and imaging simulations in combination with multiobjective optimization techniques are employed to identify the most appropriate material properties, mask, and source geometries. The resulting imaging performance is compared to the achievable performance of binary EUV masks.
CRIS-Team Scopus Importer:2019-08-16
Keywords: computational lithography; extreme ultraviolet lithography; extreme ultraviolet masks; multiobjective optimization; phase shift masks; telecentricity error; three-dimensional mask effects

Simulation study on EUV multilayer polarization effects - Bilalaj, L.; Mesilhy, Hazem Mohamed Safwat; Erdmann, Andreas (Proceedings of SPIE - The International Society for Optical Engineering, 2021)
The impact of polarization was observed in the extreme ultraviolet (EUV) imaging simulations for high NA lithography [3] [4] [5]. It is shown that polarized illumination can improve the local contrast of images or NILS (normalized intensity log slope). This work investigates the possibilities to polarize EUV light by optimized multilayers. The characterization and simulation of multilayer structures has been performed using Dr.LiTHO [10]. The most efficient multilayer polarizers operate close to Brewster angle, where the reflectivity for TM polarized light (RTM) is close to zero, according to Fresnel's equations. A multiobjective optimization algorithm was used to identify the suitable multilayer configurations maximizing reflectivity of TE polarized light (RTE) and fraction of polarization. Fraction of polarization (FoP) was calculated as the ratio between (RTE-RTM)/(RTE+RTM) to obtain the suitable multilayer with variable thickness. The multilayer structure is optimized to have the highest reflectivity of TE polarized light and fraction of polarization at the Brewster angle. It was found that MoSi multilayer can achieve 99.9% fraction of polarization by optimizing the thickness of Si and Mo. In reality, a multilayer polarizer has to operate over certain ranges of incident angles and/or wavelength ranges. Multilayer is optimized for different ranges of wavelength (13 nm: 14 nm) and incidence angles (37°: 47°). Additional simulations investigate the impact of different options in the design of the multilayer (e.g., constant vs. variable bilayer thickness) and materials (e.g., RuSi vs. MoSi multilayers) on the achievable performance.
CRIS-Team Scopus Importer:2021-11-26
Keywords: EUV Lithography; Fraction of polarization; Polarization; Reflective multilayer